Análisis de la estructura y presentación de los contenidos informativos en los noticiarios del mediodía de las radios Lluvia y Élite de la ciudad de Piñas durante el periodo octubre - diciembre de 2023. - Aguilar Galarza, Yessenia Felicia (2024)
This research begins by examining the relevance of the informative contents in the newscasts of the radio stations under study. Newscasts are journalistic spaces that have a direct impact on the formation of public opinion in their area of coverage; from this perspective, it is very important that they are structured and organized, according to the minimum rules of communication, in order to provide the audience with quality, truthful and contrasted information. With this work, it was intended to show some of the results achieved from the execution of a Research Project "Analysis of the structure and presentation of the news content in the midday newscasts of the radio stations Lluvia and Élite of the city of Piñas during the period October - December 2023", which has been carried out in two radio stations in the city of Piñas- Ecuador, namely; Radio Lluvia and Radio Élite. Among the objectives, it was intended to analyze through an exploratory-descriptive study, the structure and presentation of news content in the midday newscasts of the analyzed radios, identifying the predominant elements that are part of them and knowing the type of news content that is imparted in each of them. At the methodological level, this study had a mixed approach, focused on the use of an observation sheet to obtain relevant data on the structure and presentation of the contents, on the other hand, through the structured interview, conducted with experts and directors of the newscasts, it was intended to contrast the information obtained and thus make an objective and professional analysis around both spaces. Among the most relevant results, it was identified that both stations rely mainly on the news genre, with the news as the central component of their broadcasts, a limited diversification of sources was evidenced, depending largely on external media, which underlines the need to strengthen the internal journalistic work and promote greater autonomy in the generation of content. It is concluded that it is important to consolidate their own information base to ensure comprehensive and authentic coverage in the newscasts of these radios. This implies the need to structure the newscasts in a consistent manner, improve the quality of information and establish more rigorous standards in the production of these programs. The research addresses a relevant topic within radio communication, providing aspects that should be considered to improve journalistic quality.